Long-Term Effect of Taxation as a Fiscal Policy Instrument for National Economic Recovery - Al-hafidz, Zulfikar; Waridin, . (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
Taxation is a fiscal policy instrument that has a nearly 70% influence on the state budget and has a positive effect on the country's economy. The foundation for implementing state tax collection procedures is tax reform. Because of the pandemic situation, the government has been forced to implement tax reform (Law No. 7 of 2021) in order to prepare for the slowing national economy. The primary goal of this research is to determine how GDP responds to changes in tax instruments. GDP, government spending, the ratio of tax revenues, PPn, PPh, and government spending were used as samples from 1990 to 2020. The VAR approach was used because it can show how each variable responds to shocks from other variables. The findings indicate that the causality test occurs between the VAT variable and the tax-to-GDP ratio variable. The IRF output represents the overall GDP's positive response to shocks in each variable. Suggestions for increasing tax revenue, the government should optimize PPn and PPh as policy instruments to improve the economy in the face of the Covid-19 Pandemic.